Rehabilitation of disturbed land in bauxite mining: Challenges and prospects in Sanggau, West Kalimantan, Indonesia - Wanda, Wanda; Akbar, Aji Ali; Putri, Erisa Ayu Waspadi; Suhartoyo, Aji (Brawijaya University, 2026)
Bauxite is the primary raw material for aluminum production, and its mining activities are widespread, including in Indonesia. However, land cover changes caused by bauxite mining can significantly disrupt ecosystem balance. This study aimed to analyze land cover change rehabilitation strategies in response to bauxite mining in Sanggau Regency, Indonesia. Using Geographic Information Systems (GIS) with an overlay technique, land cover data from 2009, 2015, 2022, and 2024, along with soil quality data, were examined. The findings indicate that between 2009 and 2024, approximately 4,363.52 hectares of land were converted into mining areas, including swamp shrubland (308.67 ha), secondary swamp forest (289.28 ha), plantations (74.01 ha), primary dryland forest (3,318.92 ha), and open land (190.99 ha). Recommended rehabilitation strategies include the application of red mud waste mixed with cattle manure as fertilizer, as well as the use of cocopeat as a topsoil substitute to enhance soil quality.